Phenotypic and genetic correlations of beef replacement heifer feeding behaviour, feed intake and feed efficiency with cow performance and lifetime productivity. (28th October 2020) - Olson, Cameron A.; Li, Changxi; Block, Hushton; McKeown, Lisa; Basarab, John A.
Abstract: Objectives were to quantify the phenotypic ( r p ) and genetic ( r g ) correlations between early‐life feeding behaviours, dry matter intake, and feed efficiency and measures of cow performance and lifetime productivity traits. Traits were measured on 1, 145 crossbred replacement beef heifers and then on cows over parities one to four. Feeding event duration (FD) was phenotypically correlated with cow prebreeding body weight (PBWT; r p 0.29–0.45), cow prebreeding back fat thickness (PBBF; r p 0.35–0.49), progeny weaning weight (WW; r p 0.09–0.31) and progeny birthweight (BW; r p −0.06 to 0.17). Feeding event frequency (FF) was phenotypically correlated with PBBF ( r p 0.16–0.30). Dry matter intake (DMI) was phenotypically correlated with PBWT ( r p 0.16–0.20) and PBBF ( r p −0.22 to −0.05). Feeding event duration was genetically correlated with PBWT ( r g 0.38–0.41). Feeding event frequency was genetically correlated with PBWT ( r g −0.43 to −0.39). Dry matter intake was genetically correlated with PBWT ( r g −0.27 to 0.14). Days in herd (DIH) was phenotypically correlated with FD and DMI ( r p  = 0.12, 0.20, respectively). Lifetime productivity was phenotypically correlated with FD and FF ( r g  = 0.25, 0.22, respectively). Calving interval was phenotypically correlated with FD and FF ( r p  = −0.12, −0.14, respectively) and genetically correlated with FF ( r g  = −0.41). Due to moderate positive correlations with cow weight, caution would be required in selection to prevent an increase in mature cow size. Use of FF, FD, DMI and a measure of feed efficiency such as residual feed intake adjusted for back fat (RFIFAT ) in a balanced selection index is recommended.